Return Spillover from the US and Japanese Stock Markets to the Vietnamese Stock Market: A Frequency-Domain Approach. Issue 1 (2nd January 2021) - Nguyen, Minh Kieu; Le, Dinh Nghi
ABSTRACT: Using a frequency-domain analysis, this article examines return spillover from the US and Japanese stock markets to the Vietnamese stock market. We use daily data from the S&P 500, the Nikkei 225, and Vietnam Stock Index (VN-Index) from January 1, 2012, to December 31, 2015. A Granger-causality test is used to examine the return spillover, and the test for causality in the frequency domain by (Breitung and Candelon 2006) is used to examine the return spillover at different frequencies. The results show that significant return spillover occurs from the US to the Vietnamese stock market at all frequencies and from the Japanese to the Vietnamese stock market at higher frequencies—evidence that return spillover effects are not the same at different frequencies.